2020
DOI: 10.1177/1559325820936189
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Assessment of Multidrug Resistant Bacteria to Natural Products

Abstract: Objective: The aim of this study was to examine the effect of some natural compounds against multidrug-resistant bacteria. Methods: Forty-three bacterial strains were collected. Disc diffusion and minimum inhibitory concentration (MIC) tests were carried out for natural compounds including quercetin, Acacia nilotica, Syzygium aromaticum, and Holothuria atra. Scanning electron microscope analysis and bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…This classification is further split into several classes: tropanes, indole, purines, imidazole, pyrrolidine, pyrrolizidine, isoquinoline, piperidine, and quinolizidine [ 100 ]. More than 18,000 types of alkaloids were identified from different sources [ 101 ].…”
Section: Plant-derived Compoundsmentioning
confidence: 99%
“…This classification is further split into several classes: tropanes, indole, purines, imidazole, pyrrolidine, pyrrolizidine, isoquinoline, piperidine, and quinolizidine [ 100 ]. More than 18,000 types of alkaloids were identified from different sources [ 101 ].…”
Section: Plant-derived Compoundsmentioning
confidence: 99%
“…Prior to determining whether QEN affected S. aureus biofilm formation, available literature revealed that the MBIC of QEN on the biofilm ranged from 9 μg/ml to 60 μg/ml (Amin et al, 2015;Júnior et al, 2018;Mohamed et al, 2020). Therefore, we established 0 μg/ml, 8 μg/ml, 16 μg/ml, 32 μg/ml, 64 μg/ml, 128 μg/ml concentrations gradient to examine their MBIC value .…”
Section: The Effect Of Quercetin On Biofilm Formation In Staphylococcus Aureusmentioning
confidence: 99%
“…In addition, the list of selected gene candidates represents a starting point for further characterization of the putative biosynthetic enzymes. Eugenol is an important compound that affects the value of clove products and a biocompound with a high potential for human health benefits 21 , 53 56 . Additional studies on different organs (stems, peduncles, and roots) and specific anatomical structures (e.g., secretory cavities) will be required to further investigate the high eugenol accumulation in EO and its emission by the bud 57 .…”
Section: Discussionmentioning
confidence: 99%